Character-Based Education in the Modern Era - I Made Sadiana; Ni Nyoman Rahmawati (IAHN-TP Palangka Raya, 2026)
Character education is a crucial aspect of the education system because it plays a role in shaping students who are not only academically excellent but also possess moral integrity and social responsibility. This article aims to examine the concept of character education in the modern era, its implementation in school settings, and the various challenges faced in strengthening it. The study employs a qualitative approach using library research, analyzing various scientific articles, books, and relevant documents. The findings indicate that character education in the modern era is understood as a holistic process of internalizing values through the development of students’ moral, social, emotional, and spiritual aspects. Its implementation is achieved by integrating character values into the learning process and school culture. The main challenges faced include the development of digital technology, declining social awareness, a crisis of role models, the influence of globalization, weak synergy within the educational environment, and the dominance of an academic orientation. Therefore, it is necessary to strengthen character education in a way that is contextual, collaborative, and sustainable.